Semiotics in the Martumpol Traditional Ceremony in the Toba Batak - Febe Elnosa Kasih; Ginto Sianturi; Anggun Yuni Sarah Saragih; Revi Angel Sonata Sitorus; Jekmen Sinulingga (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to examine the forms of symbols, their semiotic meanings, and their functions within the martumpol tradition among the Toba Batak community. A qualitative method with a descriptive approach was employed, involving data collection through observation, interviews, and documentation. Data analysis was conducted using a semiotic perspective to understand the system of signs present in the martumpol procession. The results of the study indicate that the martumpol tradition encompasses various forms of symbols, such as verbal, nonverbal, material, ritual actions, and relational symbols. These symbols are interrelated and form a cohesive system of meaning within the cultural context. In semiotic analysis, the meaning of symbols in martumpol is divided into three levels: denotative, connotative, and ideological. At the denotative level, these symbols are interpreted literally, while at the connotative level, they reflect cultural values such as love, respect, and solidarity. At the ideological level, the symbols depict the norms, values, and social structures of the Batak Toba community, particularly within the dalihan na tolu kinship system. Furthermore, the symbols found in the martumpol tradition play a significant role in social life, including serving as a means to legitimize relationships, strengthen solidarity, build trust, and act as a medium for social control and cultural education. This tradition also demonstrates an adaptive nature in response to changing times without losing its fundamental meaning. Thus, martumpol functions not only as a traditional ritual but also as a tool for preserving the cultural values and identity of the Batak Toba community.